Female representation in online advertisements: a feminist stylistic analysis of beauty products advertised on Instagram - Humaira Raslie,; Aina Nadhirah Mohd Zaidi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
An advertisement is a promotional strategy to introduce a product, brand, or service to a targeted viewership; with the intent to pique their attention, encourage interaction, and ultimately, attract sales. Containing pictures, words and graphics that are familiar and present in the targeted group’s realities, advertisements, in addition to financial gains, it also greatly reflects and influences the socio-cultural construct and worldview of a community. In advertising operations carried out particularly via social media platforms, the use of language to manipulate gender depiction as an advertising strategy is recurrently observed. On this premise, this qualitative study looked into the language used in Malay advertisements for beauty products available on Instagram, a social media application. The feminist stylistic framework (Mill, 1998) served as the foundation for the textual analysis approach used to examine 150 Instagram adverts for Malay beauty goods. The stylistic features in particular were evaluated based on Verdonk (2002)'s framework, with a focus on the use of language in depicting women and the role of the language in shaping the depiction. The results demonstrated that the stylistic features utilised in Malay beauty products advertisements contained characteristics that are stereotypically assigned to women. The extensive effect of patriarchy, stereotypes, and woman sexualisation as a marketing tactic is also evident in the seller's language use. This study aims to offer evidence-based justifications for changes to be made to the existing social media advertising practice, especially in terms of language appropriateness and ethics.